The finite element method for solid and structural mechanics - 434038 Zienkiewicz, O. C.; Taylor, Robert L. (Robert Leroy), 1934- (Amsterdam, NE ; Boston : Elsevier Butterworth-Heinemann, 2005)
PSZJBL